1997
DOI: 10.1088/0953-8984/9/2/010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quantum lattice fluctuations on multiquanta Davydov-like solitons in a molecular chain

Abstract: The dressing effect due to the quantum nature of phonons may cause the creation of bound states of several vibrons in the molecular chain. The possibility of creating soliton states of this type is discussed for the simple Fröhlich one-dimensional model. The regions of the system parameter space where different mechanisms dominate the behaviour of such entities are characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…The interaction yields a stochastic modulation of each two-level system Bohr frequency by the lattice vibrations. In the exciton eigenbasis, the matrix elements of M p are expressed as (4) where…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction yields a stochastic modulation of each two-level system Bohr frequency by the lattice vibrations. In the exciton eigenbasis, the matrix elements of M p are expressed as (4) where…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Equation (4) shows that ∆H favors exciton scattering from state |k to state |k ′ via the exchange of a phonon p. The allowed transitions are specified by the selection rules M pkk ′ = 0 that generalize the concept of momentum conservation in a finite-size lattice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To interpolate between the two asymptotic solutions of the Fröhlich Hamiltonian, Brown, Ivic, and coworkers introduced a unified theory whose starting point was also based on the MLF transformation. [25][26][27][28] In the partially dressed point of view, a trial quantum state is introduced in analogy with the D 1 Davydov's ansatz. 6 Combining time-dependent variational principles and an average over the phonon degrees of freedom, the dressing fraction is finally optimized by minimizing the system ground-state energy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the dressing effect leads to an attractive interaction between vibrons mediated by virtual phonons. Such an interaction is responsible for the formation of bound states and it has been suggested that proteins can support solitons formed by bound states involving a large number of vibrational quanta [7,8,9].…”
Section: Introductionmentioning
confidence: 99%